La metodologia teologica tra dogma e Tradizione: Alfred Loisy (1857-1940) all’orizzonte billotiano - Vergano, Giancarlo (Alpha Omega, 2020)
Summary: It is a requirement of the contemporary discipline of exegesis, one which is quite marked, to be able to identify the fundamental point of departure from which to undertake the examination, from which there emerges the criterion for a historical evaluation of the Tradition. The various events and the different pronouncements which we note in the course of evolution are better explained when we discover the original impulse which gave rise to them and the motivations which determined them. Key words: evolution of dogma, Gospel, doctrines vivantes, Tradition, esprit hellénique, history. Parole chiave: evoluzione del dogma, Vangelo, doctrines vivantes, Tradizione, esprit hellénique, storia.